A stabilizing control law for invariant systems on Lie groups - Apostolou, Nikolaos; Kazakos, Demosthenes (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with the stabilizability of invariant control systems defined on Lie groups. A stabilization technique is presented which, under certain hypotheses, can lead to a criterion assuring the existence of a feedback controller which steers every initial condition to a specified target point of the state space of these systems.
Keywords: invariant systems; Lie groups; stabilization; feedback controller